Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 22, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 22, 1930. Hawley was a delegate to the republican national convention in the summer of 1872 and was chosen secretary of the committee on resolutions. Grant, of course, was renominated. Hawley was drafted in the presidential campaign as a speaker and toured much of the country. While he was in the west on a speaking trip in September Congressman Julius S. Strong of the First district died. Hawley's friends immediately got busy on his behalf. He wrote from South Bend, Ind., on September 25th, that he would run "if the demand were general and should be sustained." His friends were anxious to have him on the ground to make a definite decision, but he wired again a week later from Indianapolis that he would return in a few days and "decide congressional matter." He did return, decided in favor of becoming a candidate, was unanimously nominated and was elected.
1 electronic record. Scanned newspaper article. 2 image scans. 919 KB (941,196 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 39.8 MB (41,793,316 bytes)
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers